2022
DOI: 10.3390/electronics12010076
|View full text |Cite
|
Sign up to set email alerts
|

Wafer Surface Defect Detection Based on Feature Enhancement and Predicted Box Aggregation

Abstract: For wafer surface defect detection, a new method based on improved Faster RCNN is proposed here to solve the problems of missing detection due to small objects and multiple boxes detection due to discontinuous objects. First, focusing on the problem of small objects missing detection, a feature enhancement module (FEM) based on dynamic convolution is proposed to extract high-frequency image features, enrich the semantic information of shallow feature maps, and improve detection performance for small-scale defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For the detection of anomalies on rail surfaces, Zhang et al [1] introduce an enhanced approach employing YOLOX and image enhancement techniques for the detection of rail surface defects. The method yields a notable 2.42% improvement in the mean average precision (mAP) of the YOLOX network.Yang et al [2] combined the grayscale features of different parts of the image and proposed a rail surface segmentation method based on sliding window grayscale maximum value, achieving an improved detection accuracy of 2.78%.…”
Section: Research Reviewmentioning
confidence: 99%
“…For the detection of anomalies on rail surfaces, Zhang et al [1] introduce an enhanced approach employing YOLOX and image enhancement techniques for the detection of rail surface defects. The method yields a notable 2.42% improvement in the mean average precision (mAP) of the YOLOX network.Yang et al [2] combined the grayscale features of different parts of the image and proposed a rail surface segmentation method based on sliding window grayscale maximum value, achieving an improved detection accuracy of 2.78%.…”
Section: Research Reviewmentioning
confidence: 99%
“…Wang et al [35] designed spatial attention sharpening filters based on YOLOv5s to enhance attention to the defects at the edge location of the rail defects and constructed M-ASFF to enhance the details of the underlying features of tiny defects. Zhang et al [36] used BiFPN for feature fusion at the neck of YOLOX and also fused the NAM attention mechanism to improve the image feature expression ability, and the experimental results showed that the defect recognition rate was improved by 2.42% compared to YOLOX. Wang et al [37] addressed the problem of detecting small targets and dense occlusion on the surface of rails by introducing the SPD-Conv building block in YOLOv8 to improve detection attention to small and medium-sized targets, and the Focal-SIoU loss function was used to adjust the sample weights to improve the model's ability to recognize complex samples.…”
Section: Introductionmentioning
confidence: 99%